Improving Students’ Speaking Skill Achievement Through Tiktok Application Video - Martuah Saragih, Juni Ari; Amin, Teguh Satria (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2024)
This research aimed to improved the students’ speaking skill in English lesson by using action learning strategy. This research was conducted by using Classroom Action Research (CAR). The subject of this research was VIII-A grade of SMPS Plus Kasih Ibu Patumbak which consisted of 20 students. The objective of this research was to Improving Students’ Speaking Skill Achievement Through Tiktok Application Video. This research was conducted in two cycles which each consists’ of planning, acting, observing, and reflecting. The data were gathered through quantitative. The result showed the increasing of students score from the pre-test to post-test II. In pre-test, there was only 10 % (2 stadents) who get point . In post-test 1, there was only 35% (7 studens) who get point , 10 post-test II, there was 90 % (18 students) who get point . Besides that, TikTok Application video helped the students to created the creative class.